POTENTIAL OF MEDICINAL PLANTS FOR CANCER PREVENTION - Arif Hussain Pandith; Vicky Kumar (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
Cancer, which is defined by the body's unregulated cell multiplication, is the second-largest cause of mortality worldwide. Medicinal plants have acquired a prominent position in the treatment of countless deadly illnesses, like cancer, due to their natural phytochemicals. Herbal medications are chosen over chemical-based medications because they are medicinally highly active and cause no or few negative impacts when employed to cure ailments. Multiple types of disastrous complications can arise with chemotherapy. Several plant compounds are now being utilized to cure cancer. A wide range of plant species have been demonstrated to be effective against cancer during in vitro experiments, yet their evaluation in humans is in need of an hour. The efficacy of these botanical compounds in managing human tumors needs more research. Multiple in vitro studies using plant-derived compounds have reported apoptotic and anti-proliferative activities against different cancers. This study will explore the anticancer potential of five different plants, along with their phytochemicals.